Pulse oximetry in bronchiolitis: is it needed? - Hendaus MA; Jomha FA; Alhammadi AH (Dove Medical Press, 2015)
Mohamed A Hendaus,1,2 Fatima A Jomha,3 Ahmed H Alhammadi,1,2 1Department of Pediatrics, General Pediatrics Division, Hamad Medical Corporation, 2Weill-Cornell Medical College, Doha, Qatar; 3School of Pharmacy, Lebanese International University, Khiara, Lebanon Abstract: Infants admitted to health-care centers with acute bronchiolitis are frequently monitored with a pulse oximeter, a noninvasive method commonly used for measuring oxygen saturation. The decision to hospitalize children with bronchiolitis has been largely influenced by pulse oximetry, despite its questionable diagnostic value in delineating the severity of the illness. Many health-care providers lack the appropriate clinical fundamentals and limitations of pulse oximetry. This deficiency in knowledge might have been linked to changes in the management of bronchiolitis. The aim of this paper is to provide the current evidence on the role of pulse oximetry in bronchiolitis. We discuss the history, fundamentals of operation, and limitations of the apparatus. A search of the Google Scholar, Embase, Medline, and PubMed databases was carried out for published articles covering the use of pulse oximetry in bronchiolitis. Keywords: bronchiolitis, children, monitor, oxygen